Alteration in mitochondrial function and glutamate metabolism affected by 2-chloroethanol in primary cultured astrocytes. (December 2016) - Sun, Qi; Liao, Yingjun; Wang, Tong; Wang, Gaoyang; Zhao, Fenghong; Jin, Yaping
Abstract: The aim of this study was to explore the mechanisms that contribute to 1, 2-dichloroethane (1, 2-DCE) induced brain edema by focusing on alteration of mitochondrial function and glutamate metabolism in primary cultured astrocytes induced by 2-chloroethanol (2-CE), a metabolite of 1, 2-DCE in vivo. The cells were exposed to different levels of 2-CE in the media for 24 h. Mitochondrial function was evaluated by its membrane potential and intracellular contents of ATP, lactic acid and reactive oxygen species (ROS). Glutamate metabolism was indicated by expression of glutamine synthase (GS), glutamate–aspartate transporter (GLAST) and glutamate transporter-1 (GLT-1) at both protein and gene levels. Compared to the control group, exposure to 2-CE could cause a dose dependent damage in astrocytes, indicated by decreased cell viability and morphological changes, and supported by decreased levels of nonprotein sulfhydryl (NPSH) and inhibited activities of Na + /K + -ATPase and Ca 2 + -ATPase in the cells. The present study also revealed both mitochondrial function and glutamate metabolism in astrocytes were significantly disturbed by 2-CE. Of which, mitochondrial function was much vulnerable to the effects of 2-CE. In conclusion, our findings suggested that mitochondrial dysfunction and glutamate metabolism disorder could contribute to 2-CE-induced cytotoxicity in astrocytes, which might be related to 1, 2-DCE-induced brain edema. Graphical abstract: Highlights: Mitochondrial dysfunction was the primary event in 2-CE-exposed astrocytes (AS). Increased ROS levels caused cytotoxicity and disturb glutamate metabolism in AS. Glutamate metabolism disorder was involved in 2-CE induced cytotoxic brain edema. Mitochondrial membrane potential and activity of GS were much vulnerable to 2-CE.